PENYIMPANAN ARSIP DI KANTOR PERTANAHAN KABUPATEN SUMEDANG - Dadang Suhendi; Yudi Permana; Harry Budi Permana; Rian Nurhudin; Sindy Silvia; Tiffani Oktaviana (LPPM UNSAP & FISIP UNSAP, 2020)
his study aims to determine, obtain objective data and information regarding of archive storage at Land Office of Sumedang Regency. The research method used is a qualitative method. The sampling technique used is purposive sampling with three informants, those are: one informant from General Administration of Division of Land Legal Relations; and two informants from Assistant General Administration of Division of Land Legal Relations. The data collection techniques used are literature studies, field studies (observations, interviews, and documentations) and triangulation. The procedure of data processing uses Miles and Huberman model data analysis consisting of: data reduction, data display, and conclusion drawing/ verification. Based on the results of the study, can be concluded that archive storage at Land Office of Sumedang Regency it’s still not good. This can be seen from the temporary storage (file pending) and fixed storage (permanent file). The obstacles are, the lack of human resources; the lack of facilities and infrastructures to support archives such as shelves and file storage cabinets, and the lack of funding. Efforts that can be done are, increasing human resources in archives field, replenishment of facilities and infrastructures such as shelves and file storage cabinets, and optimizing funding.